Damage to landscape and its evaluation in Gaižiūnai military training ground - Leopoldas, Raimondas; Survilaite, Oksana; Vaitiekūnas, Petras (Journal of Environmental Engineering and Landscape Management, 2005)
The military activity carried out by the occupation army in Lithuania inflicted an extensive damage to the environment. Upon retreating the Soviet Army left enormous devastated areas, damaged soil, destroyed forests and degraded flora. In Gaižiūnai Military Training Ground it is possible to distinguish various military training territories: firing grounds, tank fields, demolition territories and tracked vehicle routes. The Ground has an artificially created terrain, devastated forms of natural landscape, compressed soil and mixed upper soil layer. Sand erosion occurs in some places. There exist strongly damaged territories in Gaižiūnai Military Training Ground (tracked vehicle route, mortar firing ground); these territories cover even 8% of the Ground. Strongly damaged territories account for 5% of the Ground (ruins in training areas 4 and 13, the former workers’ township), averagely damaged territories constitute only 1% of the Ground. Laboratory investigation shows that the soil porosity rate in the tracked vehicle route, small tank field and a drifted sand desert “Sahara” is distributed unevenly. An approximate soil porosity rate is lower by 10% than in the background territories. An evident effect of military facilities on the Ground soil is observed. When selecting measures for the soil protection against deflation, simulation of the situation was performed, building of enclosures across the prevailing wind direction of is recommended.Kraštovaizdžio pažeidimų gaižiūnų kariniame poligone vertinimasSantrauka. Okupacinės kariuomenės karinė veikla Lietuvoje padarė didžiulę žalą aplinkai. Išeidama sovietų kariuomenė milžiniškus plotus paliko nuniokotus: pažeistą gruntą, sunaikintus miškus, degradavusią augaliją. Gaižiūnų kariniame poligone galima išskirti skirtingos paskirties karinio mokymo teritorijas – šaudyklas, tankodromus, sprogdinimo teritorijas, šarvuočių trasas. Poligone sukurtas dirbtinis reljefas, suardytos natūralios kraštovaizdžio formos, suspaustas dirvožemis, sumaišytas viršutinis žemės sluoksnis. Vietomis išplitusi smėlio erozija. Labai pažeistų teritorijų yra tik Gaižiūnų kariniame poligone (šarvuočių trasa, sunkiųjų kulkosvaidžių šaudymo poligonas), šios teritorijos – net 8 % poligono ploto. Pažeistų teritorijų Gaižiūnų poligone 5 % (griuvėsiai mokymų laukuose, buvęs darbininkų miestelis), vidutiniškai pažeistų – tik 1 %. Laboratoriniai tyrimai parodė, kad šarvuočių trasos, mažojo tankodromo ir pustomo smėlio dykumos dirvožemio poringumo koeficientas pasiskirstęs netolygiai. Apytiksliai jis yra 10 % mažesnis nei foninių teritorijų. Karinės technikos poveikis poligono dirvožemiui akivaizdus. Parenkant dirvožemio apsaugos nuo defliacijos priemones, atliktas situacijos modeliavimas, rekomenduojama skersai vyraujančios vėjų krypties statyti užtvaras.Reikšminiai žodžiai: karine veikla, karinis poligonas, kraštovaizdis, dirvožemis, erozija, dirvožemio poringumas.First Published Online: 14 Oct 2010